Pendampingan Tes Dan Pengukuran Dalam Penyusunan Program Latihan Pada Perguruan Pencak Silat (PSHT) Kubu Raya - Zusyah Porja Daryanto; Muhammad Suhairi; Ade Rahmat; Ashadi Cahyadi; Nevi Hardika; Suriani Sari; Henry Maksum; Misno; Rino Lusiyono Lucius (CV. Multi Kreasi Media, 2023)
This community service is carried out with the aim of providing assistance on the importance of terminating athlete performance at the beginning before preparing a training program. This community service was carried out at the PSHT Kubu Raya Pencak Silat College at the same time as the Parit Gadoh Development Program, Sungai Kakap District. This service was carried out in several stages including: formulation of partner problems, literature review, interviews, questionnaires, implementation of activities, and FGD. The Community Service that is carried out aims to educate athletes, trainers at the pencak silat training center about the importance of knowing the initial athlete performance before giving training. So that the training given is not only regular but also measurable. The results of the community service carried out were an increase in the trainer's knowledge, and an increase in physical fitness from the training program made by looking at the athlete's initial performance.